CAPITAL GAINS FROM PRICE LEVEL INCREASES. - Nelson, Oscar S. (The Accounting Review, 1951)
Abstract The question of the distinction between operating income and capital gains was raised at the recent meetings of the American Accounting Association. Capital gains or losses are a manifestation of imperfect income measurement and result because of the requirement of modern business for periodic computation of net profit or loss. Capital gains or losses are composites of imperfect estimates of depreciation, imperfect allocations of costs, imperfect separation of capital and revenue expenditures, disregard of or imperfect adjustment for price level changes. While there is no distinction in theory between capital gains and operating income, there is a legal distinction for income tax purposes. The legal distinction is important since the tax on capital gains is less. The maintenance of the real capital of an enterprise in the face of a rising price level requires the continual upward adjustment of owners' permanent equity accounts as long term assets are consumed. This is necessary in order to restore to the business real purchasing power equivalent to that used up.